Massive haemorrhage secondary to placenta percreta in the first trimester: a case report - Abdul Hamid, Habibah; Rejali, Zulida; Mohtarrudin, Norhafizah (7847050 CANADA Inc., 2015)
Placenta percreta detected in the first trimester is a very rare condition. It is a known obstetric condition leading to serious maternal morbidity and mortality. High index of clinical suspicion and anticipation of placenta percreta is highly essential in early pregnancy as it is difficult to diagnose. The authors report on a patient who presented with heavy pervaginal bleeding in week 9 of pregnancy. Pelvic examination showed a 12-week sized uterus. Ultrasonography revealed a non-viable fetus. The subsequent emergency curettage performed was complicated by massive haemorrhage which required an abdominal hysterectomy performed as a life-saving procedure.